An Early Psychology of Science in Paraguay - García, José E. (2016)
The psychology of science is a field of research emerged in the late 80’s and its basic interest is the study of the conditions determining the rise and development of scientists and researchers. However, in spite of its apparent novelty, it is feasible to find background widely disseminated in the work of previous authors. One of them is R. Ross, who wrote an article in the Paraguayan journal Letras in 1915. Ross argued that geniuses’ production is one of the most valuable potentials to which a nation can aspire and has a relevance degree higher than any kind of wealth. His argument agrees with considerations related to the subjective processes leading creative inspiration, the generation of new ideas and the relations between genius and insanity, a view that fits the ideas of the Italian physician Cesare Lombroso. The article concludes that Ross’ ideas may be identified as a distant background for the psychology of science, although it has not reached a later continuity in the work of other Paraguayan authors. The methodology adopted is both descriptive and critical, with a contextual analysis of the primary sources that are relevant to the problem.